The visualization of three dimensional brain tumors' growth on distributed parallel computer systems - Alias, Norma; Masseri, Mohd. Ikhwan Safa; Islam, Md. Rajibul; Khalid, Siti Nurhidayah (Asian Network for Scientific Information, 2009)
The main objective of this study is to visualize the brain tumors’ growth in three-dimensional and implement the algorithm on distributed parallel computer systems. The Partial Differential Equations (PDE) to solve the mathematical problem will be discussed in this study. The growth of the brain tumor through angiogenic process is described as parabolic model in partial differential equations. The discretization of the three-dimensional parabolic equations for the brain tumor’s growth mathematical model using a numerical finite-difference method will be implemented from the previous study of two dimensional model and thus a parallelization of algorithm simulation to computational resources based on high-performance computing systems will be used to generate the growth of the brain tumor in three dimensional. The study also includes an observation of the behaviour of the cells graphically and Parallel Virtual Machine (PVM) is used to communicate the platforms involved in the computational clusters. A comparison of sequential and parallel algorithm will be discussed and this study will address the major issues of the parallel computers performance in terms of efficiency, effectiveness, speedup, and temporality.